Three essays on quality of tradable products - LU, Angdi (Institutional Knowledge at Singapore Management University, 2020)
This dissertation includes three essays on the quality of tradable products. The first chapter studies the supply-side determinants of quality specialization across Chinese cities. Specifically, we complement the quality specialization literature in international trade and study how larger cities within a country produce goods with higher quality. In our general equilibrium model, firms in larger cities specialize in higher-quality products because agglomeration benefits (arising from the treatment effect of agglomeration and firm sorting) accrue more to skilled workers, who are also more efficient in upgrading quality, although these effects are partially mitigated by higher skill premium in larger cities. Using firm-level data from China, we structurally estimate the model and find that agglomeration and firm sorting each accounts for about 50% of the spatial variation in the quality specialization. A counterfactual policy to relax land use regulation in housing production raises product quality in big cities by 5.5% and indirect welfare of residents by 6.2%. The second chapter examines how information frictions matter in the endogenous choice of product quality made by firms. We introduce quality choice into a trade-search model with information frictions Allen (2014). In our model, producers must search to learn about the quality-augmented price index elsewhere and decide whether to enter a specific destination market. Hence, a fall in information frictions such as the building of information and communications technologies infrastructure (i.e., faster mobile networks) will induce quality upgrading. We empirically test the predictions of our model using unit value data and variation in information and communications technologies infrastructure across Chinese cities. The third chapter provides empirical evidence on the effects of falling trade costs on product quality across cities within a country. We approach this question in the context of expanding the highway system in China in the past decades, which substantially reduces the trade costs across regions within the nation. Empirically, we combine two firm-level panels that provide unit-value information of products across Chinese cities with city-level data on transportation infrastructure for 2001-2007. We find that firms choose to upgrade product quality more in cities with a greater expansion of connecting highways. In addition, this effect is more pronounced in larger cities, which speaks to changes in the spatial concentration of higher-quality products. These results are also robust to the inclusion of an exhaustive battery of fixed effects and to changes in estimation specifications. Our findings shed important insights on the impact of falling intranational trade cost on quality specialization pattern across cities, which is difficult to model quantitatively due to the presence of agglomeration and sorting.